P93 The medical and surgical management of raised intraocular pressure (IOP) in children: a challenging ophthalmology case. (June 2019) - Ryan, Deirdre; Farrell, Stephen
Abstract : Background: Glaucoma is one of the most common causes of blindness in adults. In children, while it is much less common it is even more challenging to diagnose, monitor and treat. Case: 7 year old SA presented with headache on a background of Eczema and Vernal Keratoconjunctivitis. Full work up was normal, including Lumbar Puncture and CT Brain. He was poorly compliant with topical steroids prescribed for a Keratoconjunctivitis flare. On examination during Ophthalmology review, SA had conjunctival injection with corneal punctate erosions consistent with ocular surface disease. Exam was otherwise normal but difficult to perform due to photosensitivity. Symptoms improved with topical steroids, which were tapered with close monitoring as an outpatient. At two months IOPs were elevated. Steroids were discontinued and pressure reducing drops commenced. Mild hypertension was measured on subsequent visits. SA re-presented with acute photophobia and left frontal headache. IOPs were elevated at 60 mmHg (left) and 45 mmHg (right). Acetazolamide and Mannitol were administered intravenously. During examination under anaesthetic (EUA), pressure in left eye measured 34 mmHg and normal in right. The sclerae were extremely hardened. Pigment and fibrin were noted in the left anterior chamber. Left cup:disc ratio was 0.3, significantly greater than 0.1 in the right, with normal fundi. He was diagnosed with scleritis and anterior uveitis. Investigations for causes of uveitis were all negative; including Anterior Chamber Paracentesis (Herpes Simplex), MRI Brain (Vasculitis), Quantiferon Gold (Tuberculosis), Syphilis, Lyme and Bartonella serology, ANCA, serum ACE, Chest XRay. Treatment comprised oral Prednisolone, topical steroids, Acetazolamide, Latanoprost, Timolol and Dorzolamide. Inflammation resolved, pressure was reasonably controlled. Glaucoma surgery is likely to fail in the presence of active or recent inflammation, so surgical management was postponed. Despite maximum medical management SA presented a third time with raised IOP. He was brought to theatre urgently. Ahmed Valve was inserted into his left eye. Bilateral scleral calcification led to difficult valve insertion. His formal diagnosis is Idiopathic Nodular Scleritis, Intraocular Inflammation and Left Uveitic Glaucoma. Conclusion: Management of childhood glaucoma and uveitis is challenging especially in rare conditions such as this. SA's IOP is controlled, although accurate monitoring remains challenging. Rigid thickened corneas lead to falsely elevated pressures. SA developed astigmatism due to nodular scleritis involving the peripheral cornea. No progression of optic disc cupping was noted at further EUA. Despite a difficult clinical course, SA is currently asymptomatic on tapering doses of steroids and Adalizumab, enjoying an improved quality of life.